INFOBANJIR: innovative geospatial technology for flood information / Zuelaiqa Salmie Salim and Ahmad Zulhilmi Ahmad Faisal - Salim, Zuelaiqa Salmie; Ahmad Faisal, Ahmad Zulhilmi (Universiti Teknologi MARA (UiTM), 2024)
In order to deal with the increasing number of floods in Kelantan, Malaysia, flood management and early warning systems have become a necessity. This project addresses this challenge by developing a mobile application for INFOBANJIR, offering a simple interactive area map visualization connected to google maps, real-time weather updates, and emergency call button functionality. By integrating Maps, the application provides flood risk assessment and timely alerts. The system is integrated with weather data for continuous data collection, processed through sophisticated algorithms to monitor flood info setup. Dashboards and hotspots that prioritize user areas on map fragments empower users to identify hotspots at risk of flooding and take timely response actions to flood events.